TINJAUAN KINERJA PORTAL BRACING EKSENTRIS TERHADAP PEMAKAIAN TIPE LINK VERTIKAL DAN HORIZONTAL - Erwin Rommel; Yasmin Helga; Aulia Indira Kumalasari; Rizki Amalia Tri Cahyani (LPPM Universitas Negeri Jakarta, 2023)
Indonesia, which has tectonic conditions in the form of a large meeting point of the world's plates and several small plates, makes the region in Indonesia the center of earthquake occurrences and earthquake-resistant buildings are an absolute necessity. Eccentrically Braced Frames (EBFs) are a model of earthquake-resistant steel building structures that can limit inelastic behavior only to link elements, where the use of these links, especially replaceable links, can facilitate post-earthquake building repairs without having to reconstruct the main building. This study will analyze the stability, behavior, performance levels, and energy dissipation capabilities of six EBF models by combining vertical link and horizontal link configurations for different building height classifications, namely low, medium, and high buildings. Analysis uses the Response Spectrum Analysis and Pushover Analysis methods with the help of structural analysis software. From this analysis, 3-storey H-EBF has the highest stability, 10-storey V-EBF has the fastest time to reach the first yielding condition and consumes the most energy, 3-storey V-EBF has the highest ductility, and 3-storey H-EBF has the highest stiffness. highest. However, the performance level of all EBFs is in the form of Immediate Occupation and similar collapse mechanisms.